Exploring the role of traditional Chinese medicine in sarcopenia: mechanisms and therapeutic advances - Yao, Jianjun; Xia, Sheng (Frontiers in Pharmacology, 2025)
Sarcopenia is characterized by the progressive loss of muscle mass, strength, and function, predominantly affecting the elderly population, and has emerged as a significant public health concern in the context of global aging. Its pathogenesis is multifactorial, involving aging-related processes, imbalances in skeletal muscle homeostasis, mitochondrial dysfunction, immune-mediated inflammation, and gut microbiota dysbiosis. Recent studies suggest that traditional therapies, including traditional Chinese medicine (TCM)—such as herbal medicine, acupuncture, and qigong—when integrated with modern medical treatments, may offer a more personalized therapeutic approach for older adults with sarcopenia. This integrative strategy has demonstrated considerable potential to improve muscle mass, enhance strength, decelerate the aging process, and ultimately improve patients’ quality of life. This review aims to summarize the clinical research and applications of TCM in sarcopenia management, explore the potential mechanisms underlying TCM’s therapeutic effects, and discuss future research directions and their clinical relevance.